The Role of Intergenerational Communication in Local Language Preservation in Sidorejo Hamlet, Limau Village, Sembawa District, Banyuasin Regency - Aprilia , Bella; Firmansyah, Firmansyah (Communicative : Jurnal Komunikasi dan Penyiaran Islam, 2024)
The decline in the use of Javanese language among the younger generation in Sidorejo Hamlet, Limau Village, due to the influence of the environment and modern technology, which threatens the preservation of local languages and the cultural values contained in them. This research explores the role of intergenerational communication in preserving the local language in Sidorejo Hamlet. The purpose of this activity is to preserve the Javanese language through an interactive and fun approach involving children and teenagers. The method used is a descriptive qualitative approach with interviews and observations. This research was conducted in Sidorejo Hamlet, Limau Village, Sembawa District, Banyuasin Regency. The informants in this study were children and adolescents in Sidorejo hamlet. The results show that a fun and interactive approach can increase children's interest in using Javanese. The conclusion of this study is the importance of the role of families, educational institutions, and the government in preserving local languages amid the challenges of globalization. This research contributes to identifying factors that influence the preservation of Javanese language in Sidorejo Hamlet and offers practical strategies to overcome them. The implications include the importance of a comprehensive approach involving families, educational institutions, and the government as the three main pillars in local language preservation.